2013
DOI: 10.1002/bab.1121
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐based alternative method to extract bromelain from pineapple peel waste

Abstract: Bromelain is a mixture of proteolytic enzymes present in all tissues of the pineapple (Ananas comosus Merr.), and it is known for its clinical therapeutic applications, food processing, and as a dietary supplement. The use of pineapple waste for bromelain extraction is interesting from both an environmental and a commercial point of view, because the protease has relevant clinical potential. We aimed to study the optimization of bromelain extraction from pineapple waste, using the aqueous two-phase system form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Novaes et al studied the extraction of bromelain from pineapple waste, using ATPS formed by PEG and PAA. They found that the enzyme partitioned preferentially to the top/PEG‐rich phase, and the highest yield achieved was 335.27% with a purification factor of 25.78.…”
Section: Extraction and Purification Processesmentioning
confidence: 99%
“…Novaes et al studied the extraction of bromelain from pineapple waste, using ATPS formed by PEG and PAA. They found that the enzyme partitioned preferentially to the top/PEG‐rich phase, and the highest yield achieved was 335.27% with a purification factor of 25.78.…”
Section: Extraction and Purification Processesmentioning
confidence: 99%
“…The food industry produces large amounts of processing waste annually, most of which are lignocellulosic, containing a wide variety of enzymes considered critical raw materials in production and processes [255]. For example, bromelain extracted from pineapple can improve food digestion and soften beef to transform into value-added products in the market [256]. Lipases have various applications as food additives in the modification of taste, the synthesis of esters with an enjoyable antioxidant activity, hydrolysis of fats to produce detergents, wastewater treatment, and lipids removal in the cosmetic and pharmaceutical industry [257].…”
Section: Enzymesmentioning
confidence: 99%
“…The proteolysis of azocasein (1% solution in buffers at pH 6.5-7.5) results in the formation of peptides with histidine and tyrosine diazo sulphonic acid analogues that remain in solution after the reaction mixture is treated with 5-10% TCA. Azo-derived soluble peptides can be detected spectrophotometrically at 440 nm after the addition of an alkali solution with no significant interference from other colored compounds [8,19,55]. Activity measurements are usually carried out at 37 • C, both in the case of casein and azo-casein, although a number of studies have reported that the optimum temperature for stem and fruit bromelain lies in the 50-60 • C range [55].…”
Section: Bromelain Enzymatic Activity Measurementmentioning
confidence: 99%
“…Azo-derived soluble peptides can be detected spectrophotometrically at 440 nm after the addition of an alkali solution with no significant interference from other colored compounds [8,19,55]. Activity measurements are usually carried out at 37 • C, both in the case of casein and azo-casein, although a number of studies have reported that the optimum temperature for stem and fruit bromelain lies in the 50-60 • C range [55].…”
Section: Bromelain Enzymatic Activity Measurementmentioning
confidence: 99%